AKIBAT HUKUM NOTARIS YANG IKUT SERTA DALAM TINDAK PIDANA PENIPUAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 20/PK/PID/2020) - Baby Jasmine; Chairunnisa Said Selenggang (LPSDI Bina Patria, 2025)
Notary as a public official has a central role in providing legal certainty and legal protection for the community through the creation of authentic deeds. This research examines the legal consequences for notaries who participate in fraud crimes. Notaries in carrying out their duties must comply with the provisions of the Notary Position Law and the Notary Code of Ethics to maintain public trust. However, in practice, there are still notaries who commit violations or unauthorized actions in carrying out their duties and authorities. The research method used is normative juridical with a qualitative analysis approach through literature study. The results show that notaries involved in fraud crimes can be held accountable administratively, civilly, and criminally. Deeds made in violation of the law become null and void and lose their evidentiary power. Notaries may be subject to administrative sanctions in the form of oral warnings, written warnings, temporary dismissal, honorable dismissal, or dishonorable dismissal according to the level of violation committed